Transforming the rural nonfarm economy: Opportunities and threats in the developing world - Haggblade, Steven; Hazell, Peter B. R.; Reardon, Thomas (International Food Policy Research Institute, 2009)
Rural residents across the developing world earn a large share of their income—35–50 percent—from nonfarm activities. Agricultural households count on nonfarm earnings to diversify risk, moderate seasonal income swings, and finance agricultural input purchases, whereas landless and near-landless households everywhere depend heavily on nonfarm income for their survival. Over time, the rural nonfarm economy has grown rapidly, contributing significantly to both employment and rural income growth. Long neglected by policymakers, the rural nonfarm economy has attracted considerable attention in recent years. In poor agrarian countries struggling with growing numbers of marginal farmers and lackluster agricultural performance, such as those in much of Africa, policymakers view the rural nonfarm economy as a potential alternative to agriculture for stimulating rural income growth. In countries whose economies are successfully shifting from agriculture to other sectors, policymakers see the rural nonfarm economy as a sector that can productively absorb the many agricultural workers and small farmers being squeezed out of agriculture by increasingly commercialized and capitalintensive modes of farming. Given frequently low capital requirements in the nonfarm economy, policymakers in both settings view the rural nonfarm economy as offering a potential pathway out of poverty for many of their rural poor. Expectations everywhere are high. How realistic are these expectations? Can the rural nonfarm economy indeed grow rapidly enough to productively absorb a growing rural labor force? And in doing so, can it, in fact, provide a pathway out of poverty for the rural poor? A recent book published for IFPRI by Johns Hopkins University Press and Oxford University Press in India, Transforming the Rural Nonfarm Economy: Opportunities and Threats in the Developing World, marshals empirical evidence from around the globe to explore these key policy questions. The book, edited by Steven Haggblade, Peter B. R. Hazell, and Thomas Reardon, examines key factors affecting growth and equity in the rural nonfarm economy in order to identify settings and policies that favor rural nonfarm growth and enable the poor to participate in growing segments of the evolving rural nonfarm economy.